2016
DOI: 10.1080/13102818.2016.1193442
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofAspergillus nigerglucose oxidase in yeastPichia pastorisSMD1168

Abstract: The aim of this study was to establish a system for high expression of Aspergillus niger glucose oxidase (GOD) with glyceraldehyde-3-phosphate dehydrogenase gene promoter (pGAP) in Pichia SMD1168. The GOD gene from A. niger accc30161 was inserted into pGAPZaA plasmid carrying a pGAP promoter and was expressed in yeast Pichia pastoris. The expression vector, pGAPZaA-GOD, was validated by colony polymerase chain reaction (PCR), agarose gel electrophoresis, restriction enzyme analysis and sequencing methods. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…A. niger GOD can be produced by S. cerevisiae at 9 g/L. Additionally, the P. pastoris yeast expression system was successfully used to produce active GOD originating from A. niger or from P. variable P16 that was not over glycosylated (Guo et al, 2010 ; Qiu et al, 2016 ). Naturally, A. niger or Penicillium spp.…”
Section: Strategies For Improving God Productionmentioning
confidence: 99%
“…A. niger GOD can be produced by S. cerevisiae at 9 g/L. Additionally, the P. pastoris yeast expression system was successfully used to produce active GOD originating from A. niger or from P. variable P16 that was not over glycosylated (Guo et al, 2010 ; Qiu et al, 2016 ). Naturally, A. niger or Penicillium spp.…”
Section: Strategies For Improving God Productionmentioning
confidence: 99%
“…Previous studies mainly focused on the overexpression of heterologous GOD genes with strong promoters and increasing GOD gene copy numbers in P. pastoris (Belyad et al, 2018;Gao et al, 2012;Qiu et al, 2016). Furthermore, efforts have been made to improve GOD production by co-expressing genes involved in the protein folding machinery and abnormal folding stress responses, such as Hac1p (Yu et al, 2020), SEC.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Pichia pastoris enables the elimination of hyperglycosylation and secretion of heterologous proteins (Schwarzhans et al, 2017) and has been engineered for the secretory expression of GOD. Previous studies mainly focused on the overexpression of heterologous GOD genes with strong promoters and increasing GOD gene copy numbers in P. pastoris (Belyad et al, 2018; Gao et al, 2012; Qiu et al, 2016). Furthermore, efforts have been made to improve GOD production by co‐expressing genes involved in the protein folding machinery and abnormal folding stress responses, such as Hac1p (Yu et al, 2020), SEC.…”
Section: Introductionmentioning
confidence: 99%
“…GODs are produced by molds such as Aspergillus niger and Penicillium ( Frederick et al, 1990 ; Meng et al, 2014 ; Qiu et al, 2016 ; Farshad, Amin & Catherine, 2018 ). Many literatures reported that GOD could inhibit the growth of microbes in foods or food preparation media ( Tiina & Sandholm, 1989 ; Yoo & Rand, 1995 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%